PEMAHAMAN WARTAWAN HARIAN SERAM POS MALUKU TERHADAP KODE ETIK JURNALISTIK - Muskita, Marleen (Jurnal Insani, 2016)
This study aims to know the understanding Journalistic Code of Ethics by the journalist on Seram Post Daily in conduct his profession. Based on the researched problems, then here the author uses content analysis technique, as a research technique. The content analysis examines the contents of media and the problems found in the study to seek the truth.The results of this study are: understanding the ethics does not guarantee a journalist will always behave ethically, but the study of ethics is an ability that can be done every journalist so that the application can create a consistent ethical stance. The code of conduct is one of the important requirements that must be owned by journalists seeking to plunge spaciousness and make the news, but knowledge of Seram Post Daily reporter to Journalistic Code of Ethics is very less.